2021
DOI: 10.1186/s40517-021-00193-0
|View full text |Cite
|
Sign up to set email alerts
|

Economic and fault stability analysis of geothermal field development in direct-use hydrothermal reservoirs

Abstract: The installed capacity of geothermal systems for direct use of heat is increasing worldwide. As their number and density is increasing, the their interaction with subsurface faults becomes more important as they could lead to safety risks from induced seismicity. Assessment and management of such risks is essential for the further development and extension of geothermal energy for heating. At the same time, the economic output of geothermal systems can be marginal and is hence often supported by subsidy scheme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…In Eq. ( 13),μ is the coefficient of sliding friction generally ranging between 0.6 and 1.0 (Byerlee, 1978;Zaal et al, 2021). For simplicity, we consider the lower bound value of 0.6.f(μ) (Eqs.…”
Section: Thermoelastic Fracture Initiation Modelmentioning
confidence: 99%
“…In Eq. ( 13),μ is the coefficient of sliding friction generally ranging between 0.6 and 1.0 (Byerlee, 1978;Zaal et al, 2021). For simplicity, we consider the lower bound value of 0.6.f(μ) (Eqs.…”
Section: Thermoelastic Fracture Initiation Modelmentioning
confidence: 99%
“…Homogeneous and stratified reservoir models with multiple homogeneous layers have long been used for geothermal modelling purposes (Daniilidis et al, 2021(Daniilidis et al, , 2016Poulsen et al, 2015;Saeid et al, 2014). In systems where subsurface data availability is sufficient, investigating the thermal response of more realistic reservoirs is gaining more attention (Babaei and Nick, 2019;Liu et al, 2019;Mottaghy et al, 2011;Wang et al, 2020;Zaal et al, 2021). Crooijmans et al (2016), showed that a model with random, uncorrelated facies distribution overestimates lifetime compared to process-based models for N/G below 70%.…”
Section: Introductionmentioning
confidence: 99%